2016
DOI: 10.1177/0308022616672666
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evaluation of occupational therapy-led work rehabilitation for people with inflammatory arthritis: Patients’ views

Abstract: IntroductionThis qualitative study, nested in a pilot feasibility randomised controlled trial, explored the views of working people with inflammatory arthritis on the impact of a work rehabilitation programme received.MethodThirty-two participants, drawn from the 55 participants in the associated randomised controlled trial, were recruited from secondary care in the United Kingdom. Semi-structured telephone and face-to-face interviews were conducted at six (n = 32) and nine months follow-up (n = 31). Interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…We also conducted interviews with participants and the occupational therapists to investigate their views of VR and the work advice provided [ 30 , 31 ]. Intervention group participants valued the VR, particularly the training in work-based pain and fatigue self-management, joint protection, pacing, ergonomic and job adaptations/ accommodations advice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also conducted interviews with participants and the occupational therapists to investigate their views of VR and the work advice provided [ 30 , 31 ]. Intervention group participants valued the VR, particularly the training in work-based pain and fatigue self-management, joint protection, pacing, ergonomic and job adaptations/ accommodations advice.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention group participants valued the VR, particularly the training in work-based pain and fatigue self-management, joint protection, pacing, ergonomic and job adaptations/ accommodations advice. They reported: relief from discussing work problems with the occupational therapists; making behavioural adaptations at work; and improved coping skills [ 30 ]. In contrast, the control group discussed the continuing negative impact of arthritis on their work and feeling anxious about continuing working in future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then conducted an RCT (n = 55), comparing a control intervention (written self-help work advice and usual care) to JRVR plus written self-help work advice and usual care. The results of this study indicated that therapists could successfully deliver JRVR, participants considered the intervention beneficial [26], and that the JRVR intervention led to greater reductions in presenteeism (measured using the WLQ-25 at 9 month follow-up) compared to the control intervention [25]. This supported the need for a definitive trial.…”
Section: Feasibility Studymentioning
confidence: 54%
“…These difficulties differed significantly between those with co-morbid autistic spectrum disorder and those without. Prior et al (2017) explored the views of 32 people with inflammatory arthritis about an occupational therapy led job retention work rehabilitation programme they received. They considered that they were able to cope better at work and valued both the emotional support and the practical self-management education in the programme.…”
mentioning
confidence: 99%